UNDERSTANDING THE DRIVERS FOR COMMUNITY-BASED PREVENTION OF AFRICAN SWINE FEVER SPREAD: A CASE STUDY OF KASAWO AND KATOSI SUB COUNTIES, MUKONO DISTRICT, UGANDA - Savino Biryomumaisho; Geofrey Otuba; John Okongo; Frank Mwiine (Archives of Veterinary Medicine)
Pig production in Uganda is a thriving business as the demand for pork and pork products is increasing. Pork consumption per capita in Uganda is estimated to be 3.5 kg and is considered the highest in Africa. Pig production is, however, limited by several factors, including endemic diseases, particularly African swine fever (ASF), which can result in up to 100% mortality. The factors responsible for ASF outbreaks are poorly understood, especially at farm level.  A study conducted in Kasawo and Katosi sub-counties between February and March 2023 aimed to examine biosecurity and husbandry practices on pig farms. A questionnaire was distributed to pig farmers and a Focus Group Discussion (FDG) of animal health care workers was held. Blood samples were collected from pigs of all ages and sex in the two sub counties and ASF virus antibodies were tested using competitive ELISA. Out of the 777 collected blood samples, none was seropositive for ASF virus antibodies. Of the 292 households sampled, 70% kept their pigs indoors, while only 0.7% had fenced enclosures, and 4% had functional foot baths. The FGD revealed that animal health workers, who were on daily calls, carried disinfectants to sanitize their personal protective equipment (PPE) every time they left a farm. The lack of centralized slaughter facilities was identified as a key factor contributing to the spread of the ASF virus, as well as the panic selling of pigs during suspected ASF outbreaks. Sharing boars, purchasing and stocking pigs without veterinary health certification were identified as contributing factors. The results from this study showed that although active ASF infections were not found in pigs, the district experienced ASF outbreaks in the past. The study concluded that educating farmers about the spread and prevention of ASF, ensuring ongoing disinfection of PPE by animal health professionals, and establishing pig slaughter facilities could help eliminate ASF transmission and spread in the area.